Promotion Strategy Through Instagram Social Media In Increasing The Number Of Wolio Barbershop Consumers In Toraja - Susanti Susanti; Abedneigo C. Rambulangi; Mey E. Limbongan (Universitas Kristen Indonesia Toraja, 2022)
The promotion strategy is very important to implement. Especially in businesses that prioritize services because consumers must feel the benefits of services in order to carry out purchasing activities. So this study aims to determine the promotion strategy via Instagram in an effort to increase the number of Wolio Barbershop services in Makale District. This research is a qualitative research conducted at one of the SMEs in Makale District which is a barbershop named Wolio. This study used an interview instrument conducted with 7 people with details of 1 Barbershop owner, 1 Admin, and 5 Wolio Barbershop customers. The conclusion of this study states that the promotion strategy via Instagram in an effort to increase the number of Wolio Barbershop services in Makale District is due to its suitability with the Wolio Barbershop segmentation which focuses on young people who are concerned with their appearance. Especially nowadays there are so many new hairstyles that encourage the younger generation to look their best. The most dominant strategy implemented is sales promotion through special discounts such as Ramadhan Kece which provides price discounts for consumers of up to 60%. Apart from that, from Direct Marketing by making posts containing Price Lists. This means that the posts made by Wolio Barbershop contain the prices available for services at Wolio Barbershop. Constraints in efforts to increase the number of Barbershop Wolio services in Makale District include less creative Instagram content, lack of promotional costs, and no special sales team.